STRUCTURAL DESIGN OF EARTHQUAKE-RESISTANT REINFORCED CONCRETE AND STEEL FRAME ROOF IN CIBADAK BROOKPLAZA AND HOTEL - Iqbal Wiratama F, Muhammad
This final project discusses about structural design of earthquake-resistant building which will be functioned to be plaza dan hotel. This project located in Cibadak, Bandung whose soil condition is soft with high seismic acceleration, so the building classified in D seismic design category. This project has 2 podium floors as plaza, 8 floors as hotel, 2 sloors as basement, 1 floor as flat roof top, and 2 locations with steel frame roof. This structure modeled using ETABS and designed based on SNI 1726- 2019 for earthquake resistant building, SNI 1727-2013 for minimum design loads for building, SNI 2847-2019 for reinforced concrete building designs and SNI 1729-2015 for steel building structural specification. Structural design using single stage procedure which the Tower and Podium structures designed separatedly. Both Tower and Podium are special moment resisting frame system (SMF) and special structural wall system (SSW). The results of this structural design are structural analysis and earthquake resistant structural element design and steel frame roof detailing.